PENINGKATAN KEAKTIFAN MAHASISWA DAN REDUKSI MISKONSEPSI MELALUI PENDEKATAN PROBLEM BASED LEARNING - Wagiran Wagiran (Jurnal Kependidikan, 2007)
Abstract This research is trying to improve the quality of learning, reduction of misconceptions, improving of learning activity by using the method of Problem-based Learning in the subject matter of Matematika Teknik. The goal of this research is reducing as well as eradicating the students’ inactiveness in learning, reduction ofmisconceptions followed by theimprovement of learning performance. This research is a classroom action research consisting two cycles. Each cycle consists of four steps of activities: planning the action, implementation and observation, reflection and revision. Research conducted to all students participant of Matematika Teknik subject. The data were collected through observation and tests. Data were analyzed descriptively. Result of this research indicate that: (1) Learning model of Problem-Based Learning based on constructivism can reduce the frequency of misconceptions to Matematika Teknik concepts (misconceptions reduced from 87.1%  in pre-test become 41.3% at the post-test), (2) Learning model of Problem-Based Learning base on constructivism can improve students’ leaning activity marked with more and more students participate actively in learning (3) Learning model of Problem-Based Learning base on constructivism can improve learning performance of the students(from 3.3 at pre-test become 7.0 at the time of post-test). Pursuant to result of this research hence require to strive applying of learning model of Problem-Based Learning base on constructivism at broader scope in the effort of improving the quality of learning and education in applying of competence based curriculum. Keywords: Konstruktivistik, Problem-based learning, misconceptions, learning performance